Evaluating seasonal variations of fecal coliform colonization in Magallana hongkongensis and Crassostrea rhizophorae: A preliminary study of oyster quality grown in Hong Kong aquacultural farms. (May 2022) - Leung, Ho Man; Sung, Ka Chun; Peng, Xiao Ling; Cheung, Kwai Chung; Au, Chi Kin; Yung, Ken Kin Lam; Li, Wai Chin
Abstract: The objective of this research is to investigate the spatial and temporal patterns of bacteriological quality in raw oysters sampled from different aquacultural farms located in Aberdeen Typhoon Shelter, Carp Gates, Lau Fau Shan, Ma Wan, and Mui Wo in Hong Kong. Magallana hongkongensis and Crassostrea rhizophorae were collected and analyzed for fecal coliforms. Throughout the 13-month monitoring period, all samples had generally high bacterial loads, ranging from 1.4 × 10 7 cfu/g to 8.9 × 10 7 cfu/g and exceeded the guideline suggested by the HKSAR government (i.e. 700 MPN/100 g). Besides, a linear regression analysis showed that the amount of fecal coliforms in raw oysters had strong correlations (p < 0.05) to the monthly rainfall records throughout the monitoring period. Such findings illustrate the high loading of pathogenic microorganisms in the tissue of oysters which represent a potential threat of people contracting foodborne diseases. Highlights: All oyster samples had high bacterial loads. Bacterial loads in oyster substantially exceeded HKSAR government guideline. Strong correlation to bacterial load and rainfall records.